Multipliers in weighted Sobolev spaces on the axis - Myrzagaliyeva, A. (Bulletin of the Karaganda University. Mathematics Series, 2022)
This work establishes necessary and sufficient conditions for the boundedness of one variable differential operator acting from a weighted Sobolev space Wlp,v to a weighted Lebesgue space on the positive real half line. The coefficients of differential operators are often assumed to be pointwise multipliers of function spaces. The author introduces pointwise multipliers in weighted Sobolev spaces; obtains the description of the space of multipliers M(W1→ W2) for a pair of weighted Sobolev spaces (W1,W2) with weights of general type.